Analysis of the resistance to crack propagation in SENT test specimens printed in ABS using parallel or crossed filaments between layers (Fracture and Structural Integrity, 2022)
Additive manufacturing techniques continue to develop and cover all industrial fields. However, the performances of aspect and mechanical behavior of the parts obtained by this process remain to be mastered and are still the subject of current research works. Among these performances, the one corresponding to the resistance to the propagation of cracks. In order to improve this very interesting property in various industrial fields, it is desirable to master the understanding of crack propagation in this type of structure obtained by 3D printing. The objective of this paper is to analyze and understand the effect of the adopted raster angle on the crack propagation in SENT specimens obtained by FDM in ABS (Acrylonitrile-Butadiene-Styrene). Two approaches were developed: one is experimental to determine the critical stress intensity factor KIC and the other is numerical to predict the possible paths of crack propagation.
Keywords: Additive Manufacturing; FDM; Raster Angle; ABS; Crack; Numerical Simulation